Application of Vygotsky Theory in High School Mathematics Learning Material Limit Functions - Darmayanti, Rani; Usmyatun, Usmyatun; Setio, Agus; Sekaryanti, Ridina; Safitri, Niken Dwi (Universitas PGRI Madiun, 2023)
Mathematics is a subject that exists at all levels of study and requires the ability to think logically, organize, and demonstrate. One of the materials that require this ability in mathematics is the limit function material. The boundary functional material becomes the basis for mastering the next material, namely derived material. The fact that students do not have a solid understanding of the limit function literature indicates that students do not do well academically at this level. This is because students have difficulty and make mistakes in understanding concepts, facts, and procedures in the limit function literature. Vygotsky's theory can be applied to the matter of limit functions. Vygotsky applies the Zone of Proximal Development (ZPD) which is a level of development slightly above a person's current level of development. When children have learning difficulties, Vygotsky suggests that teachers can use scaffolding as support or assistance through someone who is more proficient in mastering the material to help solve problems, problems for people with higher levels of cognitive development.